2009
DOI: 10.1016/j.pupt.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Conserved responses to trichostatin A in rodent lungs exposed to endotoxin or stretch

Abstract: Histone deacetylase (HDAC) isoenzymes have been suggested as possible drug targets in pulmonary cancer and in inflammatory lung diseases such as asthma and COPD. Whether HDAC inhibition is pro-or anti-inflammatory is under debate.To further examine this clinically relevant paradigm, we analyzed 8 genes that are upregulated by two pro-inflammatory stimuli, i.e. endotoxin and mechanical stress (overventilation), in isolated rat and mouse lungs, respectively. We studied the effect of the HDAC inhibitor trichostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Recent animal studies have revealed potent anti-inflammatory effects for TSA in mouse models of allergic airways disease (AAD). TSA treatment inhibited Th2 responses, with reduced interleukin 4 (IL-4), IL-5 and immunoglobulin E (IgE) (Choi et al 2005) and attenuated airway inflammation, likely due to inhibition of T cell recruitment and Th2 cytokine production, in short-term models of AAD (Choi et al 2005;Dombrowsky et al 2009). Consistent with these anti-Th2 effects, a microarray study showed that TSA upregulated 310 genes and downregulated 313 genes, with genes for STAT5A (necessary for Th2 differentiation) and mucins (important in goblet cell metaplasia) downregulated by 80.4 and 77.3 %, respectively (Hong et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal studies have revealed potent anti-inflammatory effects for TSA in mouse models of allergic airways disease (AAD). TSA treatment inhibited Th2 responses, with reduced interleukin 4 (IL-4), IL-5 and immunoglobulin E (IgE) (Choi et al 2005) and attenuated airway inflammation, likely due to inhibition of T cell recruitment and Th2 cytokine production, in short-term models of AAD (Choi et al 2005;Dombrowsky et al 2009). Consistent with these anti-Th2 effects, a microarray study showed that TSA upregulated 310 genes and downregulated 313 genes, with genes for STAT5A (necessary for Th2 differentiation) and mucins (important in goblet cell metaplasia) downregulated by 80.4 and 77.3 %, respectively (Hong et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The ventilation-induced increase of Tnf on the other hand, was slightly stronger in C57BL/6 mice. The discrepant regulation of different genes during overventilation has been shown before in studies with trichostatin A (an inhibitor of histone deacetylase) that enhanced the transcription of Tnf and Cxcl2 , but diminished that of Il6 [38], [39]; in addition, in a cluster analysis all three genes clustered separately [39]. Another example of the discrepant regulation of Tnf and Il6 is given in ref.…”
Section: Discussionmentioning
confidence: 64%
“…The HDAC inhibitor MGCD0103 also inhibited agonist-induced contraction in the same model and also reduced antigen-and agonist-induced histamine release from rat peritoneal mast cells [128]. In other ex vivo studies using isolated rodent lungs, Trichostatin A was shown to exhibit anti-inflammatory effects reducing the stimulated release of TNF, MIP-2α, and IL-6 [129]. However, the findings from a recent in vivo study have indicated that Trichostatin A reduces airway constriction but does not have anti-inflammatory effects in mouse and human models of asthma [130].…”
Section: Histone Deacetylase Inhibitors In Experimental Models Of Asthmamentioning
confidence: 80%